Latest Ordovician age of the Spinachitina fragilis Chitinozoan Biozone in Baltoscandia - Jaak Nõlvak; Yan Liang; Olle Hints (Estonian Journal of Earth Sciences, 2023)
The global Spinachitina fragilis Chitinozoan Biozone has been considered the lowermost Silurian zone in most publications. S. fragilis was first described from the Ohesaare drill core, Estonia, and utilised as a Baltic regional zonal taxon together with Ancyrochitina laevaensis. Despite its wide geographical occurrence, S. fragilishas remained poorly documented in its type region. This has created confusion in taxonomy and distribution of the species. Herein, we have restudied material from the type locality and supplementary sections in the East Baltic region. S. fragilis generally has a very short stratigraphic range, which, according to new data on carbon isotope chemostratigraphy, coincides with the falling limb of the Hirnantian carbon isotope excursion. This suggests the latest Hirnantian rather than the early Rhuddanian age of the Spinachitina fragilis Chitinozoan Biozone in Baltoscandia. Based on this view, we revise the latest Ordovician chitinozoan biozonal scheme for the region. Globally, the S. fragilis Biozone may span across the OrdovicianâSilurian boundary.